Seismic behavior of Chuan-Dou type timber frames. (15th July 2018) - Huang, Hao; Wu, Yuntian; Li, Zhao; Sun, Zewei; Chen, Zhixiong
Highlights: Introduction to Chuan-Dou type timber structures. Seismic behavior of various forms of Chuan-Dou type timber frames. The effectivenss of light frame wood shear wall as seismic strenthening measure. Abstract: Chuan-Dou type timber constructions are popular structural systems in ancient China, which consist of planar frames jointed with mortise-tenon connection in two directions. Three types of four full scale single story and two-bay Chuan-Dou type timber frames were tested under low-cycle reversed cyclic loading. The ultimate load carrying capacity, stiffness, energy dissipation, deformation and damage characteristics were investigated. Results indicate that the Chuan-Dou type timber frame has exceptional deformation capacity, good energy dissipation capacity and poor ultimate load carrying capacity and stiffness. The load carrying capacity and stiffness of the Chuan-Dou type bare frame can be improved by infilling wattle and daub panel or light frame wood shear wall panel. Light frame wood shear wall panel can be used as a measure for seismic retrofit of Chuan-Dou type timber structures.